2020
DOI: 10.1186/s12864-020-6527-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Lactobacillus gasseri from Chinese subjects reveals a new species-level taxa

Abstract: Background: Lactobacillus gasseri as a probiotic has history of safe consumption is prevalent in infants and adults gut microbiota to maintain gut homeostasis. Results: In this study, to explore the genomic diversity and mine potential probiotic characteristics of L. gasseri, 92 strains of L. gasseri were isolated from Chinese human feces and identified based on 16 s rDNA sequencing, after draft genomes sequencing, further average nucleotide identity (ANI) value and phylogenetic analysis reclassified them as L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…In addition to genome editing, CRISPR-Cas systems have also been proven useful in probiotic research applications. The conservation of CRISPR spacer sequences has enabled the traceability and evolutionary analysis of probiotics (Barrangou and Dudley, 2016), which has been used in Lactobacillus buchneri strains genotyping (Briner and Barrangou, 2014) and new species-level taxa identification (Zhou et al, 2020). Meanwhile, the role of prophage in antibiotic resistance genes (ARGs) transfer has been revealed (Haaber et al, 2016) and prophages carrying ARGs were also found in some Bifidobacterium strains (Mancino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genome editing, CRISPR-Cas systems have also been proven useful in probiotic research applications. The conservation of CRISPR spacer sequences has enabled the traceability and evolutionary analysis of probiotics (Barrangou and Dudley, 2016), which has been used in Lactobacillus buchneri strains genotyping (Briner and Barrangou, 2014) and new species-level taxa identification (Zhou et al, 2020). Meanwhile, the role of prophage in antibiotic resistance genes (ARGs) transfer has been revealed (Haaber et al, 2016) and prophages carrying ARGs were also found in some Bifidobacterium strains (Mancino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Species that colonize diverse habitats and/or coexist with other microbes in large communities, such as many Lactobacillus species, typically have open pangenomes ( 15 ). While the majority of comparative genome studies of lactobacilli have focused on those species most relevant to the dairy industry, a recent analysis of L. paragasseri and L. gasseri considered isolates from the human gut microbiota ( 16 ). In addition to inhabiting the gut microbiota, L. paragasseri and L. gasseri are common inhabitants of the female urogenital tract, and Zhou et al ( 16 ) found that they also have an open pangenome.…”
Section: Observationmentioning
confidence: 99%
“…While the majority of comparative genome studies of lactobacilli have focused on those species most relevant to the dairy industry, a recent analysis of L. paragasseri and L. gasseri considered isolates from the human gut microbiota ( 16 ). In addition to inhabiting the gut microbiota, L. paragasseri and L. gasseri are common inhabitants of the female urogenital tract, and Zhou et al ( 16 ) found that they also have an open pangenome. Our pangenome analysis of the L. jensenii and L. mulieris strains finds that they too have an open pangenome.…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lactobacilli were isolated from human feces, and thirteen were identified as L. gasseri by 16 rDNA sequencing, showing the genetic diversity and different probiotic characteristics [ 105 ]. The resistance of L. gasseri to the human gastrointestinal tract under difficult conditions is a property that allows this microorganism to colonize the gut, improving the microbiome [ 103 , 106 ].…”
Section: Probiotics and Immunitymentioning
confidence: 99%